Human Myxomatous Mitral Valves Exhibit Focal Expression of Cartilage-Related Proteins - Carla M. R. Lacerdaa; Holly B. MacLeaa; Colleen G. Duncana; John D. Kisidaya; E. Christopher Ortona (Journal of Hypertension and Cardiology, 2013)
Background: Heart valves share developmental signaling pathways with cartilage and bone. While calcific aortic valve disease (CAVD) has been associated with valve calcification and stenosis, suggestive of osteogenesis, myxomatous mitral valve disease (MMVD) is characterized by net matrix degradation, exuberant deposition of proteoglycan, and valve regurgitation. Methods: We determined the presence of cartilage-abundant proteoglycan, aggrecan; cartilage-specific type II collagen; chondrogenic transcription factor, Sox9; and osteogenic transcription factor, Runx2 in human normal and myxomatous mitral valve leaflets by immunohistochemistry. Results and Conclusions: Myxomatous, but not normal, mitral valves demonstrated sharp focal areas that were abundant in aggrecan, type II collagen, and Sox9. These focal areas co-localized with areas of myxomatous pathologic change on Movat staining. Some cells in these areas had a round and hypertrophic morphology reminiscent of chondrocytes. Runx2 was only weakly present in normal and myxomatous mitral valves. These findings suggest a focal pathologic process in MMVD that mimics chondrogenesis.
Keywords: mitral valve